Current trends in computer data analysis - Kharin, Yuriy S.; Ablameyko, Sergey V. (Journal of the Belarusian State University. Mathematics and Informatics, 2026)
The current trends in computer data analysis presented at the conference «Computer data analysis and modelling: stochastics and data science» and the congress «Information systems and technologies» are described.